1999
DOI: 10.2134/jeq1999.00472425002800040022x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Nitrogen in Runoff following Beef Cattle Manure or Compost Application

Abstract: Manure or compost from beef cattie feediots can be an excellent sources of nutrients and organic matter when added to soils, but they can also pollute runoff. We determined the effects of simulated rainfall on runoff losses of P and N, and EC and pH following application of manure and compost to a Sharpsburg silty clay loam (fine smectitic, mesic Typic Argiudoll) soil having grain sorghum [Sorghum bicolor (L.) Moench] and winter wheat (Triticum aestivum L.) residues. Manure, compost, and fertilizer were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
129
6
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 1 publication
17
129
6
7
Order By: Relevance
“…This finding suggests that under the conditions we studied, compost and manure applied as we did would result in no more NO 3 -N loss or NH 4 -N loss in sprinkler runoff than from unamended fields. In contrast to our findings, Eghball and Gilley (1999) reported generally greater NO 3 -N loads in runoff from plots treated with compost rather than manure, and Little et al (2005) reported greater NO 3 -N and NH 4 -N loads from manured plots than controls. In both those contrasting studies, loads in simulated rainfall runoff were measured within 7 days of amendment incorporation but in our study 252 days after incorporation.…”
Section: Constituent Loads In Runoff (contrasting
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that under the conditions we studied, compost and manure applied as we did would result in no more NO 3 -N loss or NH 4 -N loss in sprinkler runoff than from unamended fields. In contrast to our findings, Eghball and Gilley (1999) reported generally greater NO 3 -N loads in runoff from plots treated with compost rather than manure, and Little et al (2005) reported greater NO 3 -N and NH 4 -N loads from manured plots than controls. In both those contrasting studies, loads in simulated rainfall runoff were measured within 7 days of amendment incorporation but in our study 252 days after incorporation.…”
Section: Constituent Loads In Runoff (contrasting
confidence: 99%
“…Delays between amendment incorporation and runoff measurement likely affected nutrient loads (Lentz and Lehrsch 2010). In the current study, NH 4 -N loads in sprinkler runoff did not differ among treatments, as was also found by Eghball and Gilley (1999) and Miller et al (2006). Phosphorus Loads.…”
Section: Constituent Loads In Runoff (supporting
confidence: 85%
See 1 more Smart Citation
“…Os valores mais elevados de CE foram observados no tratamento com dejeto líquido de suíno (DLS), sendo eles, aproximadamente, duas vezes maiores do que os observados na adubação mineral (NPK) e em torno de três vezes mais elevado do que no tratamento testemunha (T). Esses resultados podem ter sido influenciados pelo sódio (Na) presente no dejeto líquido de suíno, em decorrência de a ração fornecida aos animais conter NaCl, concordando com o observado por Eghball & Gilley (1999), os quais, avaliando a CE em diferentes sistemas de manejo do solo, com diferentes tipos de adubação, encontraram maior valor no solo que recebeu dejeto líquido de bovinos, comparado com o solo que recebeu adubação mineral. Pode-se também considerar que os resultados observados no tratamento sem adubação (T) foram expressivos (próximos dos valores do tratamento NPK), refletindo o acúmulo de nutrientes na superfície do solo sob semeadura direta, em relação ao método convencional de preparo do solo, conforme também constatado por Eghball & Gilley (1999).…”
Section: Quadro 3 Contraste De Médias Das Perdas De áGua (Lâmina De unclassified
“…Nesse mesmo trabalho, o autor observou perdas de N da ordem de 10 kg ha -1 ano -1 em áreas descobertas, enquanto, em áreas cobertas com resíduo vegetal, as perdas foram de 1 kg ha -1 ano -1 . Eghball & Gilley (1999), por outro lado, avaliando o efeito dos sistemas de semeadura direta e preparo convencional, observaram menores perdas de N na enxurrada quando o esterco bovino foi incorporado ao solo do que quando foi mantido na superfície.…”
Section: Introductionunclassified